Toward large-signal stabilization of interleaved floating multilevel boost converter-enabled high-power DC microgrids supplying constant power loads - Li, Xiangke (2023)
The interleaved floating multilevel boost converter (IFMBC), featuring high step-up ratio, high power density, low operational stress, and low current/voltage ripple, is a feasible interface to adapt low-voltage high-power energy sources to dc microgrids (MGs). However, traditional control methods can hardly ensure the stability of the IFMBC-interfaced dc MGs with tightly regulated constant power loads (CPLs) of negative and nonlinear incremental impedance. Besides, parameter uncertainties of the IFMBC will further threaten the stability of the dc MG, compromising the sustainable utilization of various energy sources. In this article, a compound large-signal stabilizer, which comprises super-twisting extended state observers and backstepping controllers, is proposed to stabilize dc bus voltage for the IFMBC interfaced high-power dc MGs with CPLs. By considering CPLs and parameter uncertainties as systematic disturbances, super-twisting ESOs can estimate the disturbances effectively during fast transients. By feeding forward the estimations, backstepping controllers are designed to accurately regulate the dc bus voltage. The large-signal stability of the dc MG is modeled and the respective results are justified by applying the Lyapunov's theorem. Simulations and experiments are performed to verify the efficacy of the proposed stabilizer.